Design of a flexible end-effector based on characteristics of tomatoes - Zhou, Kehong; Xia, Liru; Liu, Jun; Qian, Mingyan; Pi, Jie (International Journal of Agricultural and Biological Engineering, 2022)
The end-effector is the last executing part of the interaction between robots and fruits. In this paper, the physical characteristics of tomatoes and the tomato end-effector of the fluidic elastomer actuator type were studied. There was no correlation between the test point, the mass, the size and the rupture force of tomatoes. The non-destructive clamping force of tomatoes was 11.13 N. There were statistically significant correlations between the number of finger chambers, the transverse diameter of tomatoes, the inflation pressure and the clamping force. The inflation pressure and the size of tomatoes were directly proportional to the clamping force. Since fingers with more chambers had higher flexibility, the number of chambers was inversely proportional to the slope of the horizontal force-pressure curve, and the number of chambers was directly proportional to the angle between the total clamping force and the horizontal direction. A flexible end-effector was designed by genetic algorithm according to the physical characteristics of tomatoes and the simulation results of the finger of the end-effector. The test results of the end-effector showed that the tomatoes would be successfully clamped by the end-effector composed of three four-chamber fingers in a static situation with the inflation pressure less than the optimized inflation pressure (28.293 kPa). When in a dynamic situation, the success rate of tomatoes being clamped by the end-effector with an inflation pressure of 29 kPa was 97%. The tomatoes in the static clamping test and the dynamic clamping test were not damaged.Keywords: end-effector, fluid elastomer actuator, non-destructive, flexible, Genetic Algorithm, characteristics of tomatoesDOI: 10.25165/j.ijabe.20221502.6672Citation: Zhou K H, Xia L R, Liu J, Qian M Y, Pi J. Design of a flexible end-effector based on characteristics of tomatoes. Int J Agric & Biol Eng, 2022; 15(2): 13–24.